DIMENSI TUBUH SAPI BALI YANG DIPELIHARA DI TEMPAT PEMBUANGAN AKHIR SUWUNG DENPASAR DAN SENTRA PEMBIBITAN SAPI BALI DI SOBANGAN - A. K., Awang; Ariana, I N. T; Sriyani, N. L. P. (Jurnal Peternakan Tropika, 2016)
This study aimed to determine differences in body dimensions of Bali cattle raisedon Suwung landfill Denpasar and thoseraised in Bali Cattle Breeding Center in Sobangan. Each treatment consisted of 20 cows, so the research materials amounted to 40 cows with weights of 250-300 kg, aged 2-3 years. The variables observed in this study were body weight, gumba height, back height, body length, hip width and chest circumference. The results showed that gumba height, back height, hip width and chest circumference of cows raised in Sobangan were larger than those raisedon a landfill but statistically did not show significantly different results (P>0.05) while body weight and body length of cows raised in Sobangan were larger than those raisedon the landfill, and statistically they were significantly different (P<0.05).
Keywords: Body dimensions, bali cattle, landfill